Penatalaksanaan Holistik Artritis Reumatoid Pada Wanita Usia 56 Tahun Melalui Pendekatan Dokter Keluarga - M Nikhola Risol; RE. Rizal Efendi (Medula, 2020)
Rheumatoid Arthritis is an inflammatory disease due to autoimmune, systemic, progressive and chronic processes. The characteristics most frequently encountered are symmetrical polyarthritis and tenosynovitis, morning stiffness, increased blood flow rate (LED) and autoantibody images with targeted immunoglobulin (rheumatoid factor) in serum. The prevalence in men is 0.16% lower than that of women which is 0.75% and can be stated statistically significant. The cause of RA is not yet known with certainty, but there are several factors that are thought to trigger RA such as smoking, high meat consumption, infection, inflammation of the joints and tendon sheath, obesity, genetic factors, age, sex. The application evidence based medicine family doctor services for patients by identifying risk factors, clinical problems, and patient management based on the framework of solving patient problems with a patient centered and family approached approach. The analysis of study a case report. Primary data obtained through history taking, physical examination and home visits to complete family data, psychosocial and environmental data. Assessment is based holistic diagnosis from beginning, process, end study quantitatively and qualitatively. Patients have aspects internal riskknowledge about RA, curative treatment patterns, irregular eating patterns. External risk aspect patients knowledge and family support treatment, holistic management .